Peran Guru Ekonomi dalam Memanfaatkan Media Pembelajaran Visual untuk Meningkatkan Minat Belajar Siswa Kelas X SMAN 1 Lewolema 2024/2025 - Maria Enjelica Colorosa; Reinaldis Masi; Maria Fatima Bongi Beribe (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation in education demands a fundamental shift in the role of teachers from traditional instructors to modern learning facilitators who are adaptive, creative, innovative, and responsive to the latest technological developments. This research aims to explore in depth the multidimensional role of economics teachers in optimizing visual learning media to increase students' interest in learning in the digital era, especially at SMAN 1 Lewolema in the 2024/2025 academic year. Using a descriptive qualitative approach, this study involved one economics teacher and 23 students of class X through observation, interviews, and comprehensive documentation. The results show that teachers play the role of innovative learning designers, interactive facilitators who encourage active participation, motivators who arouse the spirit of learning, and innovators who make effective use of visual media. The integration of visual learning media is carried out with a contextual and interactive approach, so that it is able to transform the student learning experience holistically. The positive impacts identified include an increase in the affective dimension through a sense of pleasure, a cognitive dimension through a better understanding of the material, and a conative dimension through increased focus, interest, and motivation of students to learn. However, the implementation of the use of visual learning media cannot be separated from various challenges. Obstacles that arise include the limitations of technology infrastructure in schools, the gap in teachers' digital competencies, and the diversity of students' psychological characteristics that affect acceptance of new methods. This research makes a theoretical contribution to understanding the dynamics of educational technology integration in Indonesia, as well as offering a practical blueprint for schools with limited resources.